The theory of knowledge - Hamlyn, D.W. (New York Anchor Books, 1970)
An Introduction to the Theory of Knowledge guides the reader through the key issues and debates in contemporary epistemology. Lucid, comprehensive and accessible, it is an ideal textbook for students who are new to the subject and for university undergraduates. The book is divided into five parts. Part I discusses the concept of knowledge and distinguishes between different types of knowledge. Part II surveys the sources of knowledge, considering both a priori and a posteriori knowledge. Parts III and IV provide an in-depth discussion of justification and scepticism. The final part of the book examines our alleged knowledge of the past, other minds, morality and God. O'Brien uses engaging examples throughout the book, taking many from literature and the cinema. He explains complex issues, such as those concerning the private language argument, non-conceptual content, and the new riddle of induction, in a clear and accessible way. This textbook is an invaluable guide to contemporary epistemology.